(untitled) (Strathmore Law Journal, 2025)
The global health financing structure carries imprints of colonial-era power dynamics, perpetuating health inequities between the Global North and South. Tracing the historical origins of these inequities, this paper analyses how colonial policies and philosophies shaped early health systems to serve the interests of the European colonisers over indigenous populations in Africa. Consequently, this paper demonstrates how institutionalised racial biases from the colonial period echo in contemporary global health governance. The analysis shows the connections between historic prejudices, economic exploitation, and persisting disparities in the Global South. The author highlights how present-day inequities stem from systemic imbalances in global health financing and governance rooted in colonial mentalities. Furthermore, the author scrutinises how these colonial legacies have influenced global financial institutions and manifested in unequal resource allocation, priorities, and access—widening the global disease burden gap. The author also discusses the emergence of digital health apps and how their financing and data stewardship can risk perpetuating new forms of exploitation reminiscent of colonial extractivism. Therefore, the author argues that rectifying these structural flaws by realigning financing and governance is essential for equitable global health.